KH. M. ARWANI AMIN SEBAGAI ROLE MODEL PENDIDIKAN TAHFIDZ AL QURâ€™AN - Choeroni, Choeroni (Universitas Islam Sultan Agung, 2019)
ABSTRACTThis study focuses on the taÃfÃ al Qurâ€™an education model conducted by KH. M. Arwani in the Islamic Boarding School Yanbu'ul Holy Qur'an. The author in conducting this research uses a literature study and a qualitative descriptive approach. The results of the research that the authors did found several educational concepts memorizing the Qur'an according to KH. M. Arwani Amin, among others; 1. Sincerity, 2. ObedienceÂ 3. Importance of Quality, 4. Patience and Thoroughness. The method applied in PTYQ, namely the pesantren which he initiated as the following; 1. The musyrifahah method, 2. Recitation method, 3. takrÃŠr method, 4. MudÃ‰rasah method, and 5. Test method.While the Al-Qur'an memorization system at the pesantren which is fostered by KH. M. Arwani is divided into five groups or classes, namely: Preparation Class, Class I, Class II, Class III, and Special Classes. â€œAdabâ€œÂ learning and memorizing the Qur'an inÂ accordance with KH. M. Arwani Amin, covering adab before memorizing the Qur'an, must be based on sincerity, and adab when memorizing the Qur'an, namely; always pray and always obey all the rules of the teacher and the pesantren.Â Keywords: Al-Qur'an, Tahfidz, Education, M. Arwani Amin